Goods Asset Information System with Application (QR) Code: Study At One of The Schools in Bandung - Nur Muhammad Fadlan Fadhila; Miftah Fahmi; Rini Risanti; Asep Sudrajat; Nanang Suciyono (LPPM STMIK Mardira Indonesia, 2024)
The advancement of science and technology has enhanced the efficiency of all forms of information communication. Using two-dimensional barcodes enables the linkage between the virtual realm and the physical world, with the QR code being the most prevalent type of two-dimensional barcode. Each year, there have been significant advancements in information technology. Asset items are present in each laboratory or room of a school in Bandung. Evidence gathered at this educational institution suggests that the administration of inventory data could be more efficient. The school administrators affirm that they continue to rely on human data entry. Moreover, manual data entry is considered inefficient, and data processing tends to be sluggish. The data in question refers to the information regarding the assets. The Asset Validation application is developed utilizing the SDLC (System et al.) methodology and UML (Unified et al.) for design. The utilized programming language is PHP, or Hypertext Preprocessor, in conjunction with a MySQL database. When the URL is executed in a web browser, the system provides a description of the URL, compares it with the database, and subsequently presents it in the web browser. The outcome of the Asset Validation application is a QR code utilized to store the URL, signifying the precision of the asset item. This study also conducted a performance comparison with three analogous apps. These three comparison programs were selected based on their similar visual QR code output, although their scanning outcomes differ due to distinct features.